Piezoelectric MEMS resonators - Bhugra, Harmeet; Piazza, Gianluca (Springer Nature, 2017)
"This book introduces piezoelectric microelectromechanical (pMEMS) resonators to a broad audience by reviewing design techniques including use of finite element modeling, testing and qualification of resonators, and fabrication and large scale manufacturing techniques to help inspire future research and entrepreneurial activities in pMEMS. The authors discuss the most exciting developments in the area of materials and devices for the making of piezoelectric MEMS resonators, and offer direct examples of the technical challenges that need to be overcome in order to commercialize these types of devices. Some of the topics covered include: Widely-used piezoelectric materials, as well as materials in which there is emerging interest Principle of operation and design approaches for the making of flexural, contour-mode, thickness-mode, and shear-mode piezoelectric resonators, and examples of practical implementation of these devices Large scale manufacturing approaches, with a focus on the practical aspects associated with testing and qualification Examples of commercialization paths for piezoelectric MEMS resonators in the timing and the filter markets ... and more! The authors present industry and academic perspectives, making this book ideal for engineers, graduate students, and researchers"- Resumé vydavatel
Keywords: mikroelektromechanické systémy; piezoelektrické rezonátory; microelectromechanical systems; piezoelectric resonators; elektronické knihy; sborníky; electronic books; papers of several authors